REPUTASI KAP, KOMPLEKSITAS OPERASI, SOLVABILITAS, DAN AUDIT DELAY - Ersamayoni Wibawa, Gusti Ayu Denis; Harta Mimba, Ni Ptu Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024, 2024)
The timeliness of financial statement publication is an important factor to measure the value of a company's financial information. The phenomenon of late publication of financial statements is still found in public companies. The research objective is to determine the effect of public accountant firm reputation, operation complexity, and solvency on audit delay. The research was conducted in consumer cyclicals sector companies listed on the Indonesia Stock Exchange during the 2020-2021 period. The number of samples taken was 134 companies using non-probability sampling technique. The analysis technique used is multiple linear regression. The result showed that the public accountant firm reputation had a significant negative effect on audit delay, operation complexity had an insignificant positive effect on audit delay, and solvency had an insignificant negative effect on audit delay. The results of the research have implications for agency theory related to agency relationships between managers and owners, and practical implications for companies to consider selecting a reputable public accounting firm also provide and explain various data needed by auditors to accelerate the audit process, so that financial statement can published on time.